The Crisis Imperative Crisis Rhetoric and Welfare State Reform in Belgium and the Netherlands in the Early 1990s - Kuipers, Sanneke (Changing Welfare States, 2006)
The Netherlands and Belgium exemplified the pathology of 'welfare without work' that characterized continental welfare states - until a political crisis in both countries produced a surprising divergence in scope and extent of policy change in the early 1990s. In Belgium, government announced major reforms but its social security arrangements proved remarkably resilient. In the Netherlands, policy makers announced and implemented unprecedented cutbacks and a major overhaul of the disability benefit administration and supervision. This book argues that reform is the product of the deliberate construction of a crisis as an imperative for change. It explains how crisis rhetoric resulted in drastic policy change in the Netherlands and in incremental change in Belgium. This title is available in the OAPEN Library - http://www.oapen.org.